2018
DOI: 10.1016/j.ynstr.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

On the safety of repeated ketamine infusions for the treatment of depression: Effects of sex and developmental periods

Abstract: In this review, we will discuss the safety of repeated treatments with ketamine for patients with treatment-resistant depression (TRD), a condition in which patients with major depression do not show any clinical improvements following treatments with at least two antidepressant drugs. We will discuss the effects of these treatments in both sexes at different developmental periods. Numerous small clinical studies have shown that a single, low-dose ketamine infusion can rapidly alleviate depressive symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 128 publications
(197 reference statements)
0
27
0
3
Order By: Relevance
“…For instance, ECT (Tanney, 1986; Prudic and Sackeim, 1999; Kellner et al, 2005) and traditional interventions for suicidality require ongoing administration in order to maintain their antisuicidal effects (Valuck et al, 2009). Similarly, research suggests that ketamine also requires repeated administration in order to maintain its efficacy (Zalsman et al, 2016; Dadiomov and Lee, 2019), which is problematic given the potential for cognitive impairment and abuse with repeated administration of ketamine (Schak et al, 2016; Strong and Kabbaj, 2018). Importantly, ayahuasca is associated with a low abuse and dependence potential (Hamill et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ECT (Tanney, 1986; Prudic and Sackeim, 1999; Kellner et al, 2005) and traditional interventions for suicidality require ongoing administration in order to maintain their antisuicidal effects (Valuck et al, 2009). Similarly, research suggests that ketamine also requires repeated administration in order to maintain its efficacy (Zalsman et al, 2016; Dadiomov and Lee, 2019), which is problematic given the potential for cognitive impairment and abuse with repeated administration of ketamine (Schak et al, 2016; Strong and Kabbaj, 2018). Importantly, ayahuasca is associated with a low abuse and dependence potential (Hamill et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this meta-analysis suggests that the impact of ketamine on suicidality may begin to decrease within a week after administration. Moreover, there is no evidence that the antisuicidal effects of ketamine are long-lasting (Zalsman et al, 2016; Dadiomov and Lee, 2019) and there are significant concerns surrounding repeated administration of ketamine, including the potential for abuse and cognitive impairment (Schak et al, 2016; Strong and Kabbaj, 2018). Thus, there is a need for identifying alternative novel interventions for suicidality with less potential for abuse and a longer-lasting impact on suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the effects of sex and age on ketamine’s actions have not been broadly examined in humans, although prevalence rates and symptomatology of mental disorders associated with the glutamate system and ketamine-action, e.g., depression, significantly differ between women and men (Whiteford et al, 2013; Strong and Kabbaj, 2018; Wickens et al, 2018; Wright and Kabbaj, 2018). Although animal studies point to a variation in sensitivity to antidepressant and addictive effects of ketamine depending on age and sex (Carrier and Kabbaj, 2013; Parise et al, 2013; Franceschelli et al, 2015; Zanos et al, 2016; Schoepfer et al, 2017; Strong et al, 2017), human studies rarely report sex or age effects (Cho et al, 2005; Niciu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study found that single-dose administration is associated with immediate antidepressant effects [14]. Clinical studies have also shown that the low-dose administration of ketamine reduces the functional connectivity of the subgenual anterior cingulate cortex [15], a brain region that postmortem studies have indicated is significantly reduced in depressed patients [16]. However, the functional effects are quite complex.…”
Section: Ketamine As An Antidepressantmentioning
confidence: 99%
“…This dose and duration did not cause dependence, which was measured by drug-seeking while performing place preference conditioning tasks [14]. Most of the ketamine dependence is achieved in clinical settings with doses higher than the ones used therapeutically [15]. Most of the illicit drug users utilize multiple drugs; however, a previous report demonstrated that, in a cohort of ketamine abusers only, subjects did not exhibit changes in their cognitive capacity.…”
Section: Introductionmentioning
confidence: 95%